2006
DOI: 10.1073/pnas.0507134103
|View full text |Cite
|
Sign up to set email alerts
|

Defocused orientation and position imaging (DOPI) of myosin V

Abstract: The centroid of a fluorophore can be determined within Ϸ1.5-nm accuracy from its focused image through fluorescence imaging with one-nanometer accuracy (FIONA). If, instead, the sample is moved away from the focus, the point-spread-function depends on both the position and 3D orientation of the fluorophore, which can be calculated by defocused orientation and position imaging (DOPI). DOPI does not always yield position accurately, but it is possible to switch back and forth between focused and defocused imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
271
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(293 citation statements)
references
References 24 publications
12
271
3
1
Order By: Relevance
“…The major advantage over previous fluorescence measurements is the ability to simultaneously measure the translational step size and the lever arm's angular change. This is similar, although slightly different from (see Materials and Methods and SI Text), to what we did with myosin V (13). We find that the lever arm of the doubleheaded myosin VI indeed takes a 180°swing toward the minus end of actin, but contrary to the results of Sun et al, our data does not support a model of multiple angles of the lever arm of the lead head.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…The major advantage over previous fluorescence measurements is the ability to simultaneously measure the translational step size and the lever arm's angular change. This is similar, although slightly different from (see Materials and Methods and SI Text), to what we did with myosin V (13). We find that the lever arm of the doubleheaded myosin VI indeed takes a 180°swing toward the minus end of actin, but contrary to the results of Sun et al, our data does not support a model of multiple angles of the lever arm of the lead head.…”
contrasting
confidence: 57%
“…In this method, the focused (FIONA) and out-of-focused (DOPI) information were acquired simultaneously. This is an improvement on a previous paper where previously they were taken serially (13). (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Approaches have been developed that rely on excitation and/or emission with multiple polarizations (19,20), introduction of defocus and pattern matching (21), direct imaging of pupil functions (22), and use of annular illumination to create characteristic field distributions (23) to name a few. The alternating measurement of 2D position and orientation has also been addressed (24). Two groups considered simultaneous 2D localization and orientation fitting for molecules located in the focal plane (25) or molecules at a known defocus (26).…”
mentioning
confidence: 99%
“…The precisely metered stepping action is a function of the length of the neck (5), an extended regulatory domain of six calmodulin-binding IQ motifs that link each head to the coiled-coil tail. The favored Ϸ36-nm step allows the motor to pick out a linear pathway along a helical actin filament; however, recent work has revealed that off-axis binding can and does occur (6,7). Like other molecular motors, myosin-V works directionally, with forward steps being favored over backward steps.…”
mentioning
confidence: 99%